Demographic Status Of Adult Leukemia Patients In Sulaymaniyah, The Kurdistan Region Of Iraq (Applied Biological Research, 2023)
Leukemia is one of the most common cancer types that affects both adults and  children. The purpose of current study was to assess the demographic status of  adult leukemic patients among Kurdish population in Iraq. The records of 484  adult patients at Hiwa Cancer Hospital in Sulaymaniyah, Kurdistan region (Iraq) between January 2015 and December 2020 were the subject of this  retrospective descriptive analysis. The differenttypes of cancer observed at  Hiwa Cancer Hospital were acute lymphatic leukemia (ALL), acute myeloblastic  leukemia (AML), chronic lymphatic leukemia (CLL), and chronic myeloid  leukemia (CML). There were 307 male and 177 female cancer patients (ratio  1.734:1), with age range between 16 and 98 years and mean age of 54.49 years.  It was found that 291 (60.1%) patients were non-educated, while 109 (22.5%),  34 (7.0%), and 50 (10.3%) patients were tertiary, post-basic and basic educated, respectively. Based on the employment status, 276 (57.0%) patients were  unemployed, 145 (37.0%) employed, and 63 (13.0%) were retired. It was found  that both educational status and employment status were correlated with  leukemia incidence at p value equal to 0.0001 and 0.002, respectively.
Keywords: Demography; employment status; educational level; Iraq; leukemia incidence